PENGARUH MOTIVASI KERJA DAN KOMPENSASI TERHADAP KINERJA KARYAWAN PADA PT. BALINDO MANUNGGAL BERSAMA KOTA PALU - Putra, Udin (JURNAL ILMU MANAJEMEN UNIVERSITAS TADULAKO, 2018)
The study aims to: (1) determine and analyze simultaneous influence of work motivation and compensation on employees? performance at PT. Balindo Manunggal Bersama of Palu City; (2) determine and analyze partial influence of work motivation on employees? performance at PT. Manunggal Bersama of Palu City; (3) determine and analyze partial influence of compensation on employees? performance at PT. Balindo Manunggal Bersama of Palu City. This research uses quantitative approach to explain the relationship between two or more variables studied with a sample of 42 employees. Data analysis technique is multiple linear regressions. The results show that (1) the sig. F value of 0.002 < 0.05 means that work motivation and compensation simultaneously have significant influence on employee performance; (2) the sig. t value of 0.013<? 0.05 means that work motivation partially has significant influence on employee performance. (3) the sig. t value of 0.821>? 0.05 means that compensation has non-significant influence on employee performance.